Increasing Students’ Reading Comprehension through Advertisement At the Eighth Grader of MTs NW No. 2 Rensing In the School Year 2022/2023 - dzoharat nabila mas (khatulistiwa, 2022)
This study focused to know the effectiveness of advertisement in increasing students’ reading comprehension at the eighth graders of MTs NW No. 2 Rensing. Problem was to what extent the effect of using advertisement in increasing students’ reading comprehension. This was an experimental study. It consisted of two groups by 40 students divided into 20 students as experimental and 20 as control group. I used reading test in advertisement and hypothesis testing. Result showed that mean score in pre-test was 59.67 and 64.67 in post-test. While for standard deviation was 14.90 in pre-test and 16.60 in post-test. The lowest score in pre-test was 40 and 46.64 in post-test. While the highest score in pre-test was 100 and 100 also in post-test. The result of t-table was higher than t-table in which t-test result was 8.48 greater than t-table 2.48. Thus, t-test was higher than t-table which means teaching reading through advertisement could increase students’ reading comprehension. Hypothesis was accepted and null hypothesis was rejected